2006
DOI: 10.1161/circulationaha.106.624890
|View full text |Cite
|
Sign up to set email alerts
|

Risks Associated With Statin Therapy

Abstract: Background-Although statins reduce the risk of cardiovascular events, concerns about adverse effects may deter physicians from prescribing these agents. We performed a systematic overview of randomized statin trials to quantify the risks of musculoskeletal, renal, and hepatic complications associated with therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
129
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(136 citation statements)
references
References 72 publications
3
129
0
4
Order By: Relevance
“…However, they are not supported by the randomized controlled trial evidence: in particular, statin therapy has been found to be no less well tolerated than placebo (see below and webtable). 52,62,[236][237][238][239] As is discussed above, the potential biases inherent in studies without both randomly assigned control groups and blinded ascertainment of outcomes limit their ability to demonstrate causal associations (except for large effects on rare outcomes). This is particularly the case for symptomatic adverse events that are attributed to statin use, especially if such reports have been prompted by guidance from clinicians to their patients or from patient information leaflets and other sources.…”
Section: Other Adverse Events That Have Been Attributed To Statin Thementioning
confidence: 99%
“…However, they are not supported by the randomized controlled trial evidence: in particular, statin therapy has been found to be no less well tolerated than placebo (see below and webtable). 52,62,[236][237][238][239] As is discussed above, the potential biases inherent in studies without both randomly assigned control groups and blinded ascertainment of outcomes limit their ability to demonstrate causal associations (except for large effects on rare outcomes). This is particularly the case for symptomatic adverse events that are attributed to statin use, especially if such reports have been prompted by guidance from clinicians to their patients or from patient information leaflets and other sources.…”
Section: Other Adverse Events That Have Been Attributed To Statin Thementioning
confidence: 99%
“…Therefore, statin therapy is currently the recommended standard‐of‐care treatment for lowering LDL‐C in patients at increased CVD risk 2, 3. In contrast to all major randomized controlled trials, which have found comparable rates of muscle adverse events (AEs) between statin and placebo arms,4, 5, 6 observational studies reported higher rates of statin‐associated muscle symptoms (SAMS) in 7% to 29% of patients 7. As a consequence, patients with SAMS often receive a suboptimal statin dose or no statin therapy 7.…”
Section: Introductionmentioning
confidence: 99%
“…2). Furthermore, a review of randomized statin trials demonstrated that statin therapy is associated with a slightly increased risk of transaminase elevations, but not of myalgias, creatine kinase elevations, rhabdomyolysis, or withdrawal of therapy compared with placebo 29. Last, ASCVD is one of the most important global causes of morbidity and mortality, and the most important and clinically treatable risk factor is LDL‐C 30.…”
Section: Discussionmentioning
confidence: 99%
“…Last, ASCVD is one of the most important global causes of morbidity and mortality, and the most important and clinically treatable risk factor is LDL‐C 30. Therefore, given the favorable safety profile of statins and disastrous outcomes of CHD, the benefits of statin therapy clearly outweigh the risks of overtreatment in an era when CHD remains a world‐wide public health issue 29, 30, 31…”
Section: Discussionmentioning
confidence: 99%